Pengaruh Pemberitaan “Kasus Brigadir Yoshua” Di Media Televisi Terhadap Opini Masyarakat Kepada Kepolisian Di Perumahan OPI Kec. Jakabaring Kota Palembang - Muhammad Danil Agung PPP; Aliasan; Hasril Atieq Pohan (CV. ITTC INDONESIA, 2024)
Journalism as a news processing technique so that it is feasible to spread it to the public. A good journalist This research is based on the reporting of the Brigadier Yoshua case. Because this will definitely raise the perception of many people regarding the